Analisis Terhadap Implementasi Penanganan Parkir Liar di Kawasan Perkotaan - Farianto, Farianto (Yayasan Tri Edukasi Ilmiah, 2025)
Illegal parking is one of the serious problems in urban areas, leading to traffic congestion, a decline in city aesthetics, and disorder in public spaces. This study aims to: 1) identify the main factors causing illegal parking in urban areas; 2) examine the impacts of illegal parking on traffic and the urban environment; and 3) determine effective strategies to reduce and manage illegal parking. The research employs a qualitative approach with data collection techniques including interviews, field observations, and document studies. The findings reveal that illegal parking in urban areas is caused by limited supervision, weak law enforcement, and low public awareness. The impacts include congestion, disruption of public space functions, and a decline in urban environmental quality. Effective handling strategies require a combination of strict enforcement, public education, improved official parking facilities, and inter-agency collaboration to establish orderly and sustainable parking management. This study recommends enhancing policy socialization, strengthening regulations, and integrating digital based parking systems as sustainable solutions to the problem of illegal parking in urban areas.